AEROBIC GYMNASTIC GYMNASTICS DEVELOPMENT SURVEY, LAMPUNG PROVINCE - Latifatur R Aziz; Lungit Wicaksano; Wahyuni Hartati (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
Sports activities without realizing it or consciously are often carried out everywhere. This activity is related to physical movement, play, and recreation. Sports are sports that lead to movement activities aimed at health. aerobic gymnastic is a sport of gymnastics. The aim of this research is to know the development of aerobic gymnastic in Lampung, barriers to aerobic gymnastic exercise. government response, and supporting factors for aerobic gymnastic sports in Lampung province. The approach of this research is descriptive research, where the data collected is in the form of words, pictures, and not numbers. The instruments in this study were observation, interviews, documentation. The study was conducted orally (interview) with 4 respondents. The research location is in the Idola Pahoman Gymnastics Building, Bandar Lampung. The research data that had been collected were fully analyzed qualitatively. Result: The development of aerobic gymnastic in Lampung is good enough. Every sport will definitely need special attention from the government in the hope that the sport itself will develop and be more advanced. Conclusion of the research results: The development of aerobic gymnastic sports in Lampung, the obstacles that occur are about funding and infrastructure for aerobic gymnastic sports equipment in Lampung. The government's response to date has not provided good assistance and response. One of the supporting factors in this sport is adequate funding and infrastructure so that athlete's performance can continue to increase.